Accounting for business income in measuring top income shares. Integrated accrual approach using individual and firm data from Norway - Annette Alstadsæter; Martin Jacob; Wojciech Kopczuk; Kjetil Telle (Statistics Norway, Research Department, 2016)
Business income is important in the upper tail of the personal income distribution, but the extent to which it is captured by measures of personal income varies substantially across tax regimes. Using linked individual and firm data from Norway, we are able to attribute business income to personal owners as it accrues rather than when it is realized. This adjustment leads to an increase in top income shares, and the size of this effect varies dramatically depending on the tax regime in place. After a tax reform in 2005 that created strong incentives to retain earnings in the business, the increase is massive: accounting for earnings retained in the corporate sector leads to more than doubling of the share of income of top 0.1% in some years. As the result, traditional measures of top income shares become misleadingly low (even when accounting for capital gains). We speculate on the implications of our findings for levels and trends in top income shares observed in other countries. In particular, we note that the major tax reforms of the 1980s in the United States correspond to a shift in the direction of business income being passed through to personal owners, and argue that top income shares constructed using income tax statistics before 1987 are likely to be significantly understated relative to those afterwards.
Keywords: H3; H2; D22; G3; J3; 330; top income share; corporate income; business income; tax; inequality